SNAP benefit levels and enrollment rates by race and place: evidence from Georgia, 2007–2013. Issue 6 (2nd November 2019) - Shannon, Sarah K.S.; Bagwell Adams, Grace; Shannon, Jerry; Lee, Jung Sun
ABSTRACT: The U.S. Department of Agriculture's Supplemental Nutrition Assistance Program (SNAP) decreases poverty and food insecurity for millions of Americans. Yet not all eligible households participate, and disparities in participation exist by household size, race, ethnicity, and place. We examine the county-level associations between maximum benefit levels and SNAP enrollment by household size, race, ethnicity, and metropolitan status from 2007 to 2013 in the state of Georgia. National county-level data on participation in SNAP by racial or ethnic group are not available, but Georgia features substantial variation by race and ethnicity as well as metropolitan status at the county level that make it well suited for our analysis. Maximum SNAP benefit levels were associated with increases in county-level SNAP enrollment across the board but especially for single-person households, Hispanics, and rural Whites. These findings have implications for future changes to SNAP benefits.